ANALISIS VARIABEL-VARIABEL YANG MEMPENGARUHI PERTUMBUHAN EKONOMI DI PROVINSI KEPULAUAN BANGKA BELITUNG TAHUN 2008-2015 - Syamsu Pratama (Statistics and Data Science Program Study, SSMI, IPB University, in collaboration with the Forum Pendidikan Tinggi Statistika Indonesia (FORSTAT) and the Ikatan Statistisi Indonesia (ISI), 2019)
Economic growth of a region can assess from various aggregate sizes, one of them is GDRP (Gross Regional Domestic Product). Based on theory, GDRP can influenced by several variables, including world commodity prices which have the largest share of GDP, labor force participation rate (LFPR), Human Development Index (HDI), income inequality, open unemployment rate and percentage of the poor. In 2015 Bangka Belitung Islands Province GRDP had a share of around 0.5 percent of Indonesia's GDP. The largest share is West Bangka Regency with 11.46 trillion rupiahs, while the smallest one is East Belitung with 6.112 trillion rupiahs.To find out picture of economic growth and the influence of variable prices of palm oil commodities, LFPR, HDI income inequality, open unemployment and the percentage of the poor on economic growth in the Bangka Belitung Islands Province 2008-2015, the method used is descriptive analysis and panel data regression.The best model for estimating GDRP growth in Bangka Belitung Islands Province in 2008-2015 is the fix effect model with Seemingly Uncorrelated Regression Method. With alpha 5 percent, the variables that significantly influence economic growth are HDI, the percentage of the poor, labor force participation rate (LFPR), income inequality, open unemployment rate and world commodity prices.economic growth